Efficacy of non-pharmacological interventions for alleviating insomnia in individuals with generalized anxiety disorder: systematic evaluation and net meta-analysis - Zhang, Boyu; Li, Yiwen; Chu, Wenming; Li, Yun; Zhang, Jing; Lv, Zhenhao; Luo, Ying; Chen, Yan (Frontiers in Psychiatry, 2025)
IntroductionAnxiety is closely related to sleep, and the two often interact with each other. Generalized anxiety disorder (GAD) is often accompanied by insomnia, but pharmacologic interventions are typically ineffective and cause safety concerns. Despite the potential of non-pharmacological interventions (NIPs), their relative efficacy has not been clarified. The network meta-analysis (NMA) aims to explore the impact of NIPs on alleviating insomnia symptoms in patients with GAD.Methods and analysis24 randomized controlled trials (1,953 patients) evaluating 14 NIPs for GAD-related insomnia were utilized in this NMA. This study systematically searched the databases including PubMed, Web of Science, EMBASE, Cochran, CNKI, SinoMed, VIP, and Wanfang. Meanwhile, Bayesian method was employed in conjunction with Markov Chain Monte Carlo (MCMC) simulation. In addition, this study conducted statistical analyses by using R (version 4.4.1) and STATA (version 15.1). Interventions were ranked by standardized mean difference (SMD) and surface under the cumulative ranking curve (SUCRA); study quality was evaluated using the Cochrane Risk of Bias tool (ROB2.0). Sleep quality was assessed with Pittsburgh Sleep Quality Index (PSQI) as well as Insomnia Severity Index (ISI), and anxiety symptoms were measured using Hamilton Anxiety Scale (HAMA) and Self-rating Anxiety Scale (SAS).ResultsAcupuncture (AC) showed the best efficacy in improving sleep quality and alleviating anxiety symptoms. The combination of transcranial magnetic stimulation with psychotherapy (TMS+PT) significantly improved sleep quality and alleviating anxiety symptoms. Other interventions (e.g., relaxation therapy, exercise therapy, etc.) had limited efficacy.ConclusionAC and TMS+PT are the best NIPs to improve insomnia and relieve anxiety in GAD patients. In the future, conducting multicenter trials and in-depth mechanistic studies is expected to validate the efficacy and optimize the individualized treatment regimen.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier, CRD420251010334.